The State As The Key Actor In National Security Policy - Bagratyan, Bagrat (ՀՀ ԳԱԱ)
The essence of the state’s phenomenon lies in the fact that, due to historical experience and the specific conditions of modern political practice, the state is the most important factor in the consolidation (unification) of society. To preserve the independence, sovereignty, and territorial integrity of every country, as well as human rights, freedoms, and other important social understandings (relations), the state carries out operations aimed at ensuring national security, naturally taking into account both its own interests and those of society. The structure of ensuring the security of the Republic of Armenia is constantly and consistently being improved, based on the establishment and maintenance of the distinct status of state structures. As stages of these developments, one can distinguish the formation of the state system until 1995, the transformations of 1995–2005, the conceptual changes of 2005–2015 (2018), and the presence of entirely new governance structures from 2018 to the present. Պետության երևույթի էությունը կայանում է նրանում, որ, պատմական փորձի և ժամանակակից քաղաքական պրակտիկայի առանձնահատուկ պայմանների շնորհիվ, պետությունը հասարակության համախմբման (միավորման) ամենակարևոր գործոնն է: Յուրաքանչյուր երկրի անկախությունը, ինքնիշխանությունը և տարածքային ամբողջականությունը, ինչպես նաև մարդու իրավունքները, ազատությունները և այլ կարևոր հասարակական հասկացություններ (հարաբերություններ) պահպանելու համար պետությունն իրականացնում է ազգային անվտանգության ապահովմանը միտված գործողություններ բնականաբար հաշվի առնելով ինչպես սեփական, այնպես էլ հասարակության շահերը: Сущность феномена государства заключается в том, что, благодаря историческому опыту и специфическим условиям современной политической практики, государство является важнейшим фактором консолидации (объединения) общества. Для сохранения независимости, суверенитета и территориальной це- лостности каждой страны, а также прав и свобод человека и других зна- чимых социальных институтов (отношений), государство осуществля- ет деятельность, направленную на обеспечение национальной безопасности, естественно учитывая как свои собственные интересы, так и интересы общества.
Keywords: National Security